Uji Efektivitas Beras Herbal Forte terhadap Penurunan Kadar Glukosa Darah Pasien Diabetes Melitus Tipe 2 (Study of the Herbal Rice Forte Effectiveness on Decreasing Blood Glucose of Diabetes Mellitus Type 2 Patient) - Gema Akbar Wakhidana; Ancah Caesarina Novi Marchianti; Ali Santosa (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Diabetes mellitus is metabolic diseases characterized by hyperglycemia caused by disturbances in insulin secretion or insulin activity. Herbal Forte Rice is rice synthetic material composed of main purple sweet potato and corn flour. It contains antioksidan, fiber, resistant starch and having moderate glycemic index. This study aimed to determine the effectivity of Herbal Forte Rice on decreasing blood glucose levels of patients type 2 DM. It used a cross-over design, the role of research subjects was both as control and treatment groups. Total sample of this research consisted of 60 samples. The treatment group was given Herbal Forte Rice for 7 days in 2 consecutive meals, while the control group did not receive any intervention. The results showed the average level of Fasting Blood Glucose (FBG) beginning and end of the treatment group 179.76 mg/dL and 138.7 mg/dL; FBG beginning and end of the control 180.87 mg/dL and 187.63 mg/dL; 2 hours post prandial Blood Glucose (2hppBG) levels of beginning and end of the treatment group 284.37 mg/dL and 183.8 mg/dL; 2hppBG levels beginning and end of the control 280.57 mg/dL and 284.13 mg/dL. This study concludes that Herbal Forte Rice effective on decreasing blood glucose levels of patients type 2 DM. Keywords: diabetes mellitus, Rice Herbal Forte, GDP and GD2PP